2016
DOI: 10.18052/www.scipress.com/ilns.60.18
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Environmental and Nutritional Parameters on the Extracellular Lipase Production by <i>Aspergillus niger</i>

Abstract: Abstract. The present investigation was carried out to evaluate the effect of different growth conditions on lipase production by Aspegillus niger. The extracellular lipase producing fungus was isolated from spent bleaching earths. Optimizations of physical and chemical parameters were done for maximum lipase production using this isolate. Growth of the organism and lipase production were measured usig varying pH (4 -9), incubation temperature (20 -30 °C), incubation time (8 -80 hrs.), carbon sources, nitrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 46 publications
2
6
0
Order By: Relevance
“…A couple of studies supported the present research finding, which indicated olive oil as the most optimum inducer to aid the secretion of lipase from the local isolate. Improved lipase production from Aspergillus niger was observed when 5 % (v/v) and 1 % (v/v) olive oil were used as the inducer [22,23], which coincided with the outcomes from the present study. However, a study established coconut oil as the inducer and sole carbon source in promoting the highest lipase activity from Aspergillus tamarii.…”
Section: Optimization Of Types Of Inducersupporting
confidence: 91%
See 2 more Smart Citations
“…A couple of studies supported the present research finding, which indicated olive oil as the most optimum inducer to aid the secretion of lipase from the local isolate. Improved lipase production from Aspergillus niger was observed when 5 % (v/v) and 1 % (v/v) olive oil were used as the inducer [22,23], which coincided with the outcomes from the present study. However, a study established coconut oil as the inducer and sole carbon source in promoting the highest lipase activity from Aspergillus tamarii.…”
Section: Optimization Of Types Of Inducersupporting
confidence: 91%
“…Natural oils, namely olive oil, canola oil, coconut oil, corn oil, sunflower oil, sesame oil, and mustard oil, are often utilized as inducers for the secretion of the enzyme lipase. A high lipase yield can also be acquired from lipidic carbon sources comprising of fats and vegetable oils, which are regarded as principal sources of lipidic carbon [22].…”
Section: Optimization Of Types Of Inducermentioning
confidence: 99%
See 1 more Smart Citation
“…Further, previous studies by Mukhtar et al [48] and El-Batal et al [49] indicated that olive oil exhibits good inductive effect, whereas the present findings showed repressive effect. However, our results are in accordance with studies by Malilas et al [50], who reported the lipase production by eight fungal strains using olive oil as an inducer in SmF, which showed no noticeable lipase activity from Fusarium solani after seven days of incubation.…”
Section: Discussionsupporting
confidence: 56%
“…1,2 Thus, the scientific community gives much attention to the discovery of new and cost-effective antimicrobial agents. 3 But wide use of these agents leads to antibiotic resistance, which in turn becomes a serious issue for human health. 4 Altering the structure of bacteria and using dual-action antimicrobes are the most common techniques applied to overcome bacterial resistance.…”
Section: Introductionmentioning
confidence: 99%